S126 Dupilumab efficacy in children with uncontrolled type 2 asthma analyzed by baseline high or medium ICS dose: LIBERTY ASTHMA VOYAGE study. (11th November 2022) - Maspero, JF; Antila, MA; Jean, N; Deschildre, A; Bacharier, LB; Altincatal, A; Rimington, T; Laws, E; Akinlade, B; Radwan, A; Jacob-Nara, JA; Deniz, Y; et al.
Abstract : Introduction and Objectives: Dupilumab, a fully human monoclonal antibody, blocks the shared receptor component for interleukin (IL) 4 and IL-13, key and central drivers of type 2 (T2) inflammation, and demonstrated an acceptable safety profile and clinical efficacy in children aged 6–11 with uncontrolled moderate-to-severe asthma in VOYAGE (NCT02948959 ). This post-hoc analysis assessed dupilumab efficacy in children with T2 asthma analyzed by baseline inhaled corticosteroid (ICS) dose in children with T2 asthma (baseline blood eosinophils ≥150 cells/μL or baseline fractional exhaled nitric oxide ≥20 ppb). Methods: Children received weight-based dupilumab 100/200 mg every 2 weeks or placebo and were stratified by medium (n=195) or high (n=152) baseline ICS dose per GINA 2015 guidelines. In a prespecified, multiplicity-controlled analysis, annualized severe asthma exacerbation rates (AER) over the 52-week treatment period in the high ICS group were evaluated. Other prespecified analyses were AER in the medium ICS group, and, in both groups, changes from baseline in pre-bronchodilator (BD) percentage predicted (pp) FEV1 and interviewer-administered 7-Item Asthma Control Questionnaire (ACQ-7-IA) score. Results: Baseline AER in dupilumab/placebo patients were 3.04/2.56 in the high and 2.27/1.88 in the medium ICS groups. Dupilumab vs placebo significantly reduced AER by 63% ( P =0.0004) and 59% ( P =0.0028) in the high and medium ICS groups, respectively. Dupilumab improved pre-BD ppFEV1 in both high (LS mean difference, 5.70 [0.99, 10.40]; P =0.0180) and medium (9.35 [4.38, 14.33]; P =0.0003) ICS groups at Week 52. Reductions from baseline in ACQ-7-IA scores at Week 12 were significantly greater with dupilumab vs placebo in the high ICS group (-0.58 [−0.84, −0.33]; P <0.0001) and numerically greater in the medium ICS group (−0.18 [−0.41, 0.05]; P =0.1317) at Week 12. By Week 52 significant improvements in ACQ-7-IA were seen with dupilumab vs placebo in both the high (−0.53 [−0.75, −0.31]; P <0.0001) and medium (−0.40 [−0.60, −0.20]; P =0.0001) ICS groups. Conclusion: Dupilumab demonstrated clinical efficacy in children with uncontrolled moderate-to-severe type 2 asthma regardless of ICS dose at baseline, with significant reductions in exacerbations as well as significant improvements in lung function and asthma control by end of treatment. Please refer to page A212 for declarations of interest related to this abstract.